1986
DOI: 10.1538/expanim1978.35.4_531
|View full text |Cite
|
Sign up to set email alerts
|

A Serological Survey on 15 Murine Pathogens in Mice and Rats

Abstract: A serological survey for 15 murine pathogens was performed on 269 mouse sera collected from 21 conventional and 12 barrier colonies, and on 376 rat sera collected from 21 conventional and 23 barrier colonies.Animals having an antibody against at least one of the antigens were contained in 81.0% of conventional and 16.7% of barrier mouse colonies and also in 81.0% of conventional and 43.5% of barrier rat colonies. Main contaminants were mouse hepatitis virus and Sendai virus in mice, and Sendai virus and pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…Paturzo, et al, [19] reported that RV could be detected in the explanted culture of several organs from infant which were inoculated with the virus 14 weeks before and from juveniles inoculated 7 weeks before, even after seroconversion. In present study, neither the infectious virus nor the viral antigen was detected in any organs of the surviving newborns 4 weeks after inoculation (data not shown Serological surveys [6,8,10] have shown that specific antibodies were found in the contaminated colonies with RV at a high incidence up to 100% and that the virus was maintained for long periods. Therefore, high prevalence of passive immunity in newborn rats could be suspected, which will prevent fatal infection with RV, although newborns proved to be highly susceptible to the RV.…”
Section: Discussioncontrasting
confidence: 53%
“…Paturzo, et al, [19] reported that RV could be detected in the explanted culture of several organs from infant which were inoculated with the virus 14 weeks before and from juveniles inoculated 7 weeks before, even after seroconversion. In present study, neither the infectious virus nor the viral antigen was detected in any organs of the surviving newborns 4 weeks after inoculation (data not shown Serological surveys [6,8,10] have shown that specific antibodies were found in the contaminated colonies with RV at a high incidence up to 100% and that the virus was maintained for long periods. Therefore, high prevalence of passive immunity in newborn rats could be suspected, which will prevent fatal infection with RV, although newborns proved to be highly susceptible to the RV.…”
Section: Discussioncontrasting
confidence: 53%
“…A , and Europe [7,131, and measures should be taken to prevent rodents reared in research and breeding facilities from the infection. Nude mice have been shown to be highly susceptible to PVM exhibiting a severe form of the disease [19,211. In Japan, evidence of PVM infection in mice and rodents was reported in 1986 by Parker's original HI test using a commercial antigen [9]. The present study disclosed that treatment with RDE is essential to remove non-specific HA inhibitor (s), revealing that the significance of the low antibody titer detected without RDE treatment in 1986 is obscure.…”
Section: Resultsmentioning
confidence: 65%
“…In these cases, serum samples were not treated with a receptor destroying enzyme (RDE). Moreover, the significance of the low antibody titer detected in HI test was not clear [9]. As the presence of a nonspecific HA inhibitor in normal animal sera was well known in cases of infection with other myxoviruses [2], paramyxoviruses [5,61 and togaviruses [3,11,18], RDE treatment has become to be a common procedure to remove HA inhibitor (s) from human and animal sera in HI tests of these viruses.…”
mentioning
confidence: 99%
“…For the ELISAs using SeV-NP peptides, the dilution ratio of sera was 1:200, which was higher than that of the commercial ELISA. The antigen in the commercial ELISA was ether-treated entire SeV virions [18,19] [4]. We considered that the ELISAs using the SeV-NP peptides might be suitable for the wild house mouse, which is the same species as laboratory mice.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme linked-immunosorbent assay (ELISA) is the most common serological assay for the detection of SeV-infection [9,26]. To date, mature virions are usually used as antigens in ELISAs for the detection of anti-SeV antibodies [18,19]. However, a false-positive result may be obtained, because of cross-reactivity between antibodies present in sera and non-specific antigens derived from contaminated microorganisms used in the ELISA.…”
mentioning
confidence: 99%